The Influence of The Interaction Between Urea and Super Phosphate Fertilizers on Some Morphological and Physiological Characteristics of Wheat - Aziz Alarkawizi, Aso L. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An experiment was carried out by using pots in kalar horticulture station/ Sulaimani province on soil which is talken form on once region field in the seasoning growth(20062007). The objective was to study interaction of different levels from urea fertilizer (zero, 0.20, 0.40, 0.80 gm / 4 kg soil in pot). These levels were equal to (zero, 25, 50, 100, kg uera / D) and super phosphate levels (zero, 0.24, 0.48, gm / 4 kg soil in pot).These levels were equal to(zero, 30, 60, kg / D) in morphological and physiological characteristies (ex. dry weight, leaf area, absolute growth rate, protein percentage, and chlorophyll content) of Ipa (95) wheat variety. This experiment was carried out by completely Randomized Design (C. R. D.). Results indicated a clear increase in all the studied characteristics with the increase of urea and super phosphate levels added to the pots. The levels (100 kg urea / D and 60 kg super phosphate / D) were best in giving high values of these characteristics comparative with other levels from these fertilizers.